Pravopisna načela v slovenskem pravopisu - Unuk, Drago (Revija za elementarno izobraževanje, 2009)
Ortographic principles in the Slovenian ortography. The term orthography is used here in the narrow sense of the word and refers to the use of grapheme units. Orthography is a collection of general principles and specific rules that govern the marked sound of a language (i.e.phonemes) with written signs (graphemes). Thus, orthographic rules function as markers. Furthermore, the function of orthographic instructions is to convey knowledge: they enable language users to get acquainted with written signs and their connection to the effects of sounds and their meanings. The article presents various orthographic principles (phonetic, phonological, morphological, etymological and historical orthographic). The selection and practice of a certain orthographic principle is the result of the connection with the development of literacy in an individual language. In the Slovene language, consonants are written according to the morphophonological and phonological principles, sound alterations according to the phonetic principle, and some sporadic phenomena realiyed according to etzmological and historical principles. Another particular aspect of Slovene language, besides the way consonants are written, is the writing of vowels, since it does not follow the phonetic orthographic principle or the phonological or morphophonological principle. It follows traditions and is therefore a result of tradition, i.e. the historical orthographic principle. Consequently, in Slovene orthography, an explicit deficiency or inaccuracy in the writing of vowels can be observed.